RANCANG BANGUN SISTEM INFORMASI MANAJEMEN JOB PLACEMENT CENTER POLITEKNIK NEGERI SUBANG - Mohammad Iqbal; Slamet Rahayu (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Job Placement Center is a job application system using the internet as a media that connects between job seekers, information about a job with companies / agencies that need labor. This study aims to design an online recruitment system using a rapid application development (RAD) model in which the system is perceived to be more effective and efficient than conventional recruitment media such as newspapers, advertisements, and so on. All companies / institutions that need workers can share information related to a job in accordance with certain criteria, such as position / age, age, achievement index, gender, and so on. This information can be accessed by alumni and students of Subang State Polytechnic. Employment providers can get all information related to the curriculum vitae of the candidates so that they can get the best candidates. Keywords: Information System , Rapid Application Development, Recruitment